2022
DOI: 10.1161/jaha.121.023294
|View full text |Cite|
|
Sign up to set email alerts
|

Sex Differences in Recovery and Device Replacement After Left Ventricular Assist Device Implantation as Destination Therapy

Abstract: Background The relevance of sex and preimplant factors for clinical outcomes among patients with left ventricular assist devices intended for destination therapy is unclear. Methods and Results INTERMACS (Interagency Registry for Mechanically Assisted Circulatory Support) data (2006‐2017) from 6771 men and 1690 women with left ventricular assist devices as destination therapy were analyzed to evaluate the contribution of preimplant clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Inflammatory markers, which have been linked to cardiovascular morbidity, may be higher in women 49,50 . Women may also be socioeconomically disadvantaged, 51 face disadvantageous gender roles, 18 and have higher rates of depression, all risk factors for cardiovascular morbidity 52 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inflammatory markers, which have been linked to cardiovascular morbidity, may be higher in women 49,50 . Women may also be socioeconomically disadvantaged, 51 face disadvantageous gender roles, 18 and have higher rates of depression, all risk factors for cardiovascular morbidity 52 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this disparity poses questions as to whether men may benefit more from LVAD implantation than women. As a caveat, it is worth noting that there may be a bridge‐to‐transplant selection bias; some reports suggest that women on bridge‐to‐transplant receive delayed transplants compared to men, which may contribute to their higher mortality rates post‐LVAD 18 . Also, one study has found that post‐LVAD recovery was better in women, although this was partially due to female‐specific causes of HF that are likely more easily reversed 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of the Journal of the American Heart Association ( JAHA ), Maukel and colleagues 4 reviewed the INTERMACS (Interagency Registry for Mechanically Assisted Circulatory Support) database for sex differences in clinical outcomes. From 2006 to 2017, 6771 men and 1690 women underwent cfLVAD implantation in the framework of destination therapy.…”
mentioning
confidence: 99%
“…Regardless of demographic and psychosocial characteristics, women experienced significantly more device complications requiring replacement than men. 4 …”
mentioning
confidence: 99%